PENERAPAN METODE DISKUSI DALAM MENINGKATKAN PEMAHAMAN GLOBALISASI - Sri Rahayu Pudjiastuti; N. Ilis; Hesti Mustika Ati (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
THE APPLICATION OF DISCUSSION METHODS IN INCREASING UNDERSTANDING OF GLOBALIZATIONDuring learning through online media, the learning process is centered on the teacher while students only listen to and accept concepts, communication occurs in one direction and students are not given the opportunity to build their own knowledge so that student activity in learning is low, student involvement is limited to completing the tasks given by teacher. The research objective is to obtain new theories and effective discussion methods on how to improve students' understanding of globalization material. The research method used is classroom action research. The results of the research in the first cycle used the discussion method with the source of the textbook, the average result was 61.67. The second cycle used the discussion method with material sources not only from Citizenship Education textbooks but students doing book reviews with references other than textbooks related to globalization material, there was an increase, namely 73.33. The third cycle using the discussion method with newspaper clipping media sources, obtained an average result of 79, 17 thus the average student has reached the specified Minimum Completeness Criteria, namely 65. According to the students the discussion method makes them not tense and feel comfortable, from the results assessment of students in cycle one, 37.05% of students can achieve the minimum standard value, 74.08% in second cycle, and 92.7% of the third cycle. This study concludes that newspaper clipping media has a significant impact on student learning development. From the results of student interviews, it was found that the discussion method can make students dare to express their opinions because there is good communication within their groups.